2015
DOI: 10.1080/14780887.2015.1050748
|View full text |Cite
|
Sign up to set email alerts
|

“Because You’re Worth It”: A Discourse Analysis of the Gendered Rhetoric of the ADHD Woman

Abstract: Drawing on the traditions of discursive psychology and critical discourse analysis this study examined the presentation of attention deficit hyperactivity disorder (ADHD) in women in a sample of the most commonly identified online YouTube videos on this topic. The video material selected represented a combination of first-person testimonies from the "sufferer" and the sharing of "expertise" by "professionals." Analysis involved the identification of common rhetorical devices and evaluation of the role of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The use of the word “severe” makes the reader observe characteristic differences between the normal and the abnormal child. The definition of abnormal behaviors is, however, a result of social decision-making, and a sharp line between normal and abnormal behaviors is illusory as pointed out by Börjesson ( 1999 ) and Winter et al ( 2015 ). Nevertheless, attempts to engage the reader in a critical debate about what constitutes “severe” behaviors are lacking in the analysed document.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of the word “severe” makes the reader observe characteristic differences between the normal and the abnormal child. The definition of abnormal behaviors is, however, a result of social decision-making, and a sharp line between normal and abnormal behaviors is illusory as pointed out by Börjesson ( 1999 ) and Winter et al ( 2015 ). Nevertheless, attempts to engage the reader in a critical debate about what constitutes “severe” behaviors are lacking in the analysed document.…”
Section: Resultsmentioning
confidence: 99%
“…Winter, Moncrieff, and Speed ( 2015 ) performed a discourse analysis of how “ADHD” was depicted on YouTube by women who had received the diagnosis. Their analysis showed how the women positioned themselves in the biomedical discourse and even promoted the “ADHD” diagnosis.…”
mentioning
confidence: 99%
“…These adults reported having developed more positive self-perceptions, less self-blame, and more self-forgiving attitudes toward themselves after being diagnosed. Winter et al (2015) similarly found that women diagnosed with ADHD optimistically proposed on YouTube that ADHD enabled them to live more productive lives and that medication maximized their potential.…”
Section: Socially Accepted Identitymentioning
confidence: 98%
“…Once diagnosed, these adults narrated the ability to reconstruct their perceptions to create a more coherent and comprehensible view of their difficulties in the past and in the present. In a study by Winter, Moncrieff, and Speed (2015) women diagnosed with ADHD positioned themselves on YouTube in the medical discourse by using vocabulary adapted from the medical discourse when describing themselves.…”
Section: Sense Of Coherencementioning
confidence: 99%
“…Based on their findings the researchers concluded that the media provides an unobjectionable view of the medicalization of child behavior. As medical prescriptions for ADHD are found to be disproportionally high in socioeconomic disadvantaged areas (Harwood, 2010; Watson, Arcona, Antonuccio, & Healy, 2014), a broader discussion in the media on the medicalization and the diagnosis of ADHD should be encouraged (Gonon, Konsman, Cohen, & Boraud, 2012; Winter, Moncrieff, & Speed, 2015). …”
mentioning
confidence: 99%